The deduced structure of the T cell receptor gamma locus in Canis lupus familiaris. - MASSARI, SERAFINA; F. Bellahcene; Giovanna Vaccarelli; G. Carelli; Michaela Mineccia; Marie Paul Lefranc; Rachele Antonacci; Salvatrice Ciccarese (Molecular Immunology, 2009)
Analyzing the recent high-quality genome sequence of the domestic dog (Canis lupus familiaris), we deduced for the first time in a mammalian species belonging to Carnivora order, the genomic structure and the putative origin of the TRG locus. New variable (TRGV), joining (TRGJ) and constant (TRGC) genes for a total of 40 are organized into eight cassettes aligned in tandem in the same transcriptional orientation, each containing the basic recombinational unit V-J-J-C, except for a J-J-C cassette, that lacks the V gene and occupies the 3' end of the locus. Amphiphysin (AMPH) and related to steroidogenic acute regulatory protein D3-N-terminal like (STARD3NL) genes flank, respectively, the 5' and 3' ends of the canine TRG locus that spans about 460kb. Moreover LINE1 elements, evenly distributed along the entire sequence, significantly (20.59%) contribute to the architecture of the dog TRG locus. Eight of the 16 TRGV genes are functional and belong to 4 different subgroups. Canine TRGJ genes are two for each cassette and only seven out of 16 are functional. The germline configuration and the exon-intron organization of the 8 TRGC genes was determined, six of them resulting functional. The dot plot similarity genomic comparison of human, mouse and dog TRG loci highlighted the occurrence of reiterated duplications of the cassettes during the dog TRG locus evolution. On the other hand the low ratio of functional genes to the total number of canine TRG genes (21/40), suggest that there is no correlation between the extensive duplications of the cassettes and a need for new functional genes. Furthermore the comparison revealed that the TRGC6, C7 and C8 genes are highly related across species suggesting these existed before the primate-rodent-canidae lineages diverged.